Impact of gender on perceptual fit evaluation for prestige brands - Lau, K.; Phau, Ian (Palgrave Macmillan, 2010)
This article examines the impact of gender on perceptual fit evaluation of prestige brands. Using an experimental approach, this study demonstrates that elaboration effects derived from schema congruity and self-congruity have an impact on perceptual fit and are moderated by the consumer's gender. More specifically, women have the ability to establish stronger brand personality fit and brand image fit, which is reflective of their greater sensitivity in recognizing brand images and personality dimensions that match their self-concept. However, it is also shown that the nature of the task or effort for processing messages would have an impact on one's selection of strategy for processing information. Advertising professionals have to consider the gender of their target consumers when they design advertisements for their extension brands in the prestige brand category. Branding professionals should also consider the effect of schema congruity between advertisements of parent and extension brands on target consumers of both genders.